Global economic effects of US biofuel policy and the potential contribution from advanced biofuels. Issue 6 (November 2012) - Oladosu, Gbadebo; Kline, Keith; Leiby, Paul; Uria-Martinez, Rocio; Davis, Maggie; Downing, Mark; Eaton, Laurence
Background: This study evaluates the global economic effects of the current US RFS2, and the potential contribution from advanced biofuels.Results & discussion: Our simulation results suggest that these mandates lead to an increase of 0.21% in the global gross domestic product in 2022, including an increase of 0.8% in the USA and 0.02% in the rest of the world, relative to our baseline no-RFS scenario. The incremental contributions to gross domestic product from advanced biofuels in 2022 are estimated at 0.41 and 0.04% in the USA and the rest of the world, respectively.Conclusion: Although production costs of advanced biofuels are higher than for conventional biofuels in our model, their economic benefits result from reductions in oil use and their smaller impacts on food markets compared with conventional biofuels. Thus, the US advanced biofuels targets are expected to have positive net economic benefits.